ANALYSIS IMPACT OF THE EXPANSION OF THE REGION AGAINST LOCAL COMMUNITY SOCIAL CONFLICT - Baso Madiong (Indonesia Prime, 2016)
Research entitled the influence of the expansion Area of the cultural values of society of West Sulawesi province aims to study the formation mechanism of the new autonomous region, as well as more healt not neglecting the terms that have been determined. and that is not less important is the readiness of the region concerned, both in aspects of the financing, human Resources and the credibility of the bureaucracy in the management of good governance and better. the other thing is to do the capacity of the public to control the performance of the Executive and the legislature which is especially representative of the people who tend to exploit the people. so that the spirit of the sea area bottom line is improving public services and rich people and does not pose a conflict of cultures really manifested in a more benevolent and wise. The method used is the guidance to the Government and society in General about the real purpose of the expansion area as well as coaching the community who are in conflict due to the expansion region.